Improvement of the bacteriological method for isolation of Listeria monocytogenes - Mikhail V. Khramov; Lyubov V. Domotenko; Olga V. Polosenko; Irina P. Mitsevich (Журнал микробиологии, эпидемиологии и иммунобиологии)
Introduction. Currently, listeriosis is regarded as one of the dangerous infections that cannot be prevented by vaccination and is characterized by the severity of the clinical process and high mortality. Improving laboratory diagnostic methods especially in listeriosis meningitis to identify the pathogen in the shortest possible time remains an urgent problem.